2007
DOI: 10.1111/j.1365-2249.2007.03539.x
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin, a functional compound of liquorice, attenuates colonic inflammation in mice with dextran sulphate sodium-induced colitis

Abstract: SummaryInflammatory bowel disease (IBD) is characterized by detrimental immune reactivity in the gut, and the imbalance between proinflammatory and antiinflammatory reactivity. The aims of this study were to determine whether oral administration of glabridin, a functional component of liquorice, could ameliorate dextran sulphate sodium (DSS)-induced colitis, as well as to understand the possible underlying mechanisms. Acute experimental colitis was induced in BALB/c mice by treatment with 5% DSS for 7 days. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 38 publications
5
62
0
1
Order By: Relevance
“…The results demonstrated that the mRNA expression of these infl ammatory mediators are dose-dependently suppressed by glabridin treatment, suggesting that the inhibitory effect of glabridin on the production of NO, TNF-α and IL-1β might be mediated by the inhibition of mRNA expression of cognate genes. Consistent with our results, Kwon and coworkers recently reported that glabridin attenuates colonic infl ammation by inhibiting the expression of infl ammatory mediators, such as NO, PGE 2 and TNF-α (Kwon et al, 2008). It was also reported previously that glabridin inhibits NO production and iNOS gene expression in mouse peritoneal macrophages and RAW 264.7 cells, a mouse macrophage cell line (Kang et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrated that the mRNA expression of these infl ammatory mediators are dose-dependently suppressed by glabridin treatment, suggesting that the inhibitory effect of glabridin on the production of NO, TNF-α and IL-1β might be mediated by the inhibition of mRNA expression of cognate genes. Consistent with our results, Kwon and coworkers recently reported that glabridin attenuates colonic infl ammation by inhibiting the expression of infl ammatory mediators, such as NO, PGE 2 and TNF-α (Kwon et al, 2008). It was also reported previously that glabridin inhibits NO production and iNOS gene expression in mouse peritoneal macrophages and RAW 264.7 cells, a mouse macrophage cell line (Kang et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…In differentiated adipocytes, glabridin stimulated AMPK phosphorylation and decreased expression of proinfl ammatory genes in the presence of TNF ␣ , a potent infl ammatory inducer. Consistent with these data, glabridin exhibits anti-infl ammatory responses in colitic subjects ( 60 ). Therefore, it appears that glabridin-induced AMPK might also contribute to the suppression of infl ammatory responses, which would lead to improvements in metabolic disorders, such as insulin resistance in obesity.…”
Section: Glabridin Affects Mitochondrial Functions and Cellular Amp/asupporting
confidence: 58%
“…7 The root of Glycyrrhiza glabra (licorice) has been used for many centuries in Asia and Europe as an antioxidant, antidote, demulcent, expectorant, and a remedy for allergic inflammation, as well as a flavoring and sweetening agent. 8 Glabridin, an active isoflavan in the hydrophobic fraction of licorice root, 9,10 is easily incorporated into the gut cells and released to the basolateral side by aglycone form in human 1 and mice. 11,12 It has shown multiple biological activities, such as antibacterial, neuroprotective, antiatherosclerotic, antiosteoporosis, and immunomodulatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It has shown multiple biological activities, such as antibacterial, neuroprotective, antiatherosclerotic, antiosteoporosis, and immunomodulatory activities. [9][10][11][12][13][14][15][16][17] Studies have shown that glabridin exhibits growth inhibition properties against breast cancer cells. 17 It also enhances the efficacy of cancer chemotherapy by inhibiting P-glycoprotein and multidrug resistance protein 1 synthesis.…”
Section: Introductionmentioning
confidence: 99%